‘Another Place, Another Feeling’: Narrating the Emotional Geography of an Indonesian English Teacher - Rizky Apriliyanti; Arini Nurul Hidayati; Yusup Supriyono; Fuad Abdullah (UIR Press, 2021)
Commencing his teaching career as a university students’ English teacher in a religious surrounding, Harry, with his free-will and open-minded personality, has experienced a turbulent feeling. He was sometimes confused to situate himself in certain situations which turned him out to be a little bit more clunky. Within the framework of Hargreaver’s (2001) emotional geography, this present study explores the life of Harry amidst his two years teaching experience at one university in Tasikmalaya, West Java, Indonesia. This scrutiny was geared by employing in-depth interviews. Utilizing narrative inquiry as the research methodology, the researchers share the stories of Harry when updating into a novel teaching and cultural circumstance and delving into his emotional ups and downs. The findings of this study revealed five major issues, namely (1) Harry needs to be more careful when engaging with the students (2) teaching is the work of the soul, no matter what (3) exhaustion is very human, (4) experienced-based teaching practice, and (5) having supportive colleagues truly help.